2009
DOI: 10.1016/j.juro.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Citrate Therapy on the Risk of Renal Stone Formation During Spaceflight

Abstract: Results from this investigation suggest that supplementation with potassium citrate may decrease the risk of renal stone formation during and immediately after spaceflight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 10 publications
3
35
1
2
Order By: Relevance
“…Despite the use of exercise, decreases in bone density and bone strength, together with muscle volume, continue to occur in crewmembers during long-duration missions on the ISS (Convertino, 2002;Holick, 1998;Keyak et al, 2009;Lang et al, 2004;LeBlanc et al, 2000LeBlanc et al, , 1998Whedon et al, 1974;Trappe et al, 2009). The risks associated with these deleterious effects of microgravity include bone fracture, renal stone formation, increased fatigue, decreases in strength, and limited physical working capacity (Whitson et al, 2009;Convertino and Sandler, 1995;Convertino, 2002). Data from the first 6 expeditions on-board the ISS indicated that bone mineral density (BMD) was lost at a monthly rate of 1.4-1.5% at the hip and 0.9% at the spine (Lang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of exercise, decreases in bone density and bone strength, together with muscle volume, continue to occur in crewmembers during long-duration missions on the ISS (Convertino, 2002;Holick, 1998;Keyak et al, 2009;Lang et al, 2004;LeBlanc et al, 2000LeBlanc et al, , 1998Whedon et al, 1974;Trappe et al, 2009). The risks associated with these deleterious effects of microgravity include bone fracture, renal stone formation, increased fatigue, decreases in strength, and limited physical working capacity (Whitson et al, 2009;Convertino and Sandler, 1995;Convertino, 2002). Data from the first 6 expeditions on-board the ISS indicated that bone mineral density (BMD) was lost at a monthly rate of 1.4-1.5% at the hip and 0.9% at the spine (Lang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological, environmental, and dietary conditions imposed by space travel and weightlessness have a considerable potential for increasing the risk of renal stone development (11,26,(37)(38)(39)40). CaOx stones account for ϳ85% of the clinical occurrences of nephrolithiasis on Earth, and the majority of the 14 stones developed by the astronauts postflight (13,26,33).…”
mentioning
confidence: 99%
“…Citrate is one of the main contributors to urine's intrinsic inhibitory capacity (40,42). It can protect against CaOx crystallization in two ways.…”
mentioning
confidence: 99%
“…These renal data form the basis of the third subject designated as a "microgravity astronaut." Finally, the last subject represents a microgravity stone former and was constructed using the long-duration flight data provided by Whitson et al (38) as extracted from the 24-h postflight (return ϩ 0 -2) urine samples obtained from astronauts who were subject to the placebo test. In this case, the SDs associated with the respective excretion rates were used to construct a hypothetical "worst case" microgravity scenario as given by the entries for this case in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There are other contributing factors such as the astronauts' high protein and sodium level that in addition to inducing higher calcium and pH levels can also provide nidi that may serve as nucleation sites, thus promoting CaOx precipitation (37,41). The higher pH levels will also lower the concentration of citrate, one of the primary inhibitors of CaOx growth and agglomeration (38,41). In short, alterations in the renal biochemistry of astronauts tend to provide favorable conditions for increased nucleation, growth, and agglomeration of CaOx crystals in the renal system.…”
mentioning
confidence: 99%